PENGARUH VARIABEL EKONOMI TERHADAP KRIMINALITAS DI INDONESIA - Isna Zahra; Umaruddin Usman (LPPM Universitas Malikussaleh – Indonesia, 2023)
This study examined the effect of open unemployment, income inequality, and population density on crime in Indonesia using panel data analysis. The scope of this research covers 5 provinces in Indonesia for 10 years (2010-2019). The regression tool in this study used Eviews 9. The results showed that the open unemployment rate positively and significantly influenced crime in Indonesia, income inequality positively and significantly influenced criminality in Indonesia, and population density positively and significantly influenced criminality in Indonesia.